Down-Regulation of TRPM5s During the Development of the Rat Neocortex and Hippocampus - Sun, F.P.; Gao, T.M. (Нейрофизиология, 2013)
The transient receptor potential (TRP) superfamily of cation membrane channels includes
a large number of recently identified protein molecules that share the sequence homology
with the Drosophila protein named after a phototransduction mutant of this insect called
trp. Believing that one or more TRP channels might be involved in the process of neural
development, we examined the possibility by searching the full profile of TRPC17, TRPV16,
TRPM18, and TRPA1 channels during the development of the neocortex and hippocampus
of rats (from the embryonic state to adults). The RTPCR experiment was performed with
mRNA isolated from the abovementioned cerebral structures. Developmental changes were
identified in transcripts for the profiles of TRPC17, TRPV16, TRPM18, and TRPA1.
Downregulation of exclusively TRPM5, whose mRNA expression level gradually decreased
in the course of pre and postnatal development of both neocortex and hippocampus, was
the most striking finding. Our results suggest that TRPM5s might have some important
function in neural development. There is a possibility that TRPM5s are key components of
the physiological function for sensing the environmental temperature in the developmental
period of rats. Суперсімейство мембранних катіонних каналів транзієнтного рецепторного потенціалу (TRP) включає в себе велику
кількість нещодавно ідентифікованих канальних протеїнів,
у котрих первинні послідовності є гомологічними такій у
протеїну мутанта дрозофіли, отриманого в результаті фототрансдукції та названого trp. Вважаючи, що один або більше типів TRPканалів можуть бути задіяними в процес розвитку нервової системи, ми намагалися дослідити повні часові профілі представленості каналів TRPC17, TRPV16,
TRPM18 та TRPA1 у перебігу розвитку неокортексу та гіпокампа у щурів (від ембріонального стану до дорослого
віку). Зворотна рескриптаза – полімеразні ланцюгові реакції (ЗРПЛР) були проведені зі зразками мРНК, виділеними
зі згаданих структур. Пов’язані з розвитком зміни були ідентифіковані в транскриптах для профілів TRPC17, TRPV1
6, TRPM18 та TRPA1. Найбільш вражаючим випадком
була негативна регуляція (downregulation) тільки кількості
TRPM5; рівень експресії їх мРНК поступово зменшувався
в перебігу пре та постнатального розвитку як неокортексу,
так і гіпокампа. Наші результати дають досить переконливі підстави вважати, що TRPM5 можуть виконувати якусь
важливу функцію в онтогенетичного розвитку нервової системи. Розглядається можливість того, що TRPM5 є ключовими компонентами в системі сприйняття температури середовища в початковий період онтогенезу щурів.